Effect of pioglitazone treatment on serum chemerin and vaspin levels in polycystic ovary syndrome. - Rana Hussein Kutaif; Mustafa G. Alabbassi; Weqar Akram Hussein; Zainab Faleh Ali; Shatha Khayun Jassim (College of Pharmacy / Mustansiriyah University, 2022)
Abdominal fat synthesizes a variety of adipokines, including vaspin and chemerin, that affect the resistance to insulin. This research was conducted to demonstrate the effect of pioglitazone, one insulin sensitizer used to decrease insulin resistance, on these adipokines in   obese patients with polycystic ovary (PCOS). Twenty-five obese women with PCOS were treated with pioglitazone 15mg/bid for 12 weeks. Modifications in fasting blood glucose (FBG), serum fasting insulin (FSI), chemerin and vaspin serum levels, follicle stimulation hormone (FSH), luteinizing hormone (LH), testosterone (T), and in baseline and post-therapy were assessed. Body mass index decreased without any substantial variance after 12 weeks of pioglitazone therapy (P> 0.05). T, FSI, HOMA-IR, LH, and FBG levels have decreased considerably (P≤0.01, P≤0.05) after the therapy. No substantial variations were found in FSH (P>0.05). Serum chemerin and vaspin levels were observed no significant difference than before treatment (P>0.05) in obese women with polycystic ovarian syndrome cases.